Luxembourg’s Expanding Higher Education System: Responding to Global Norms - Braband, Gangolf; Powell, Justin J.W. (International Higher Education, 2016)
Luxembourg has an expanding higher education system, with one of the youngest European national research universities at its center. The University of Luxembourg was founded, against local resistance, as an elite institutional response to global norms and to the Europe-wide Bologna Process.